Kajian literasi informasi mahasiswa di UIN Sunan Ampel Surabaya sebagai dasar pengembangan layanan perpustakaan - Sulaiman Sulaiman; Suprapto Suprapto (IJAL (Indonesian Journal of Academic Librarianship), 2019)
ENGLISH This study aims to examine how information literacy of students at UIN Sunan Ampel Surabaya. Information literacy is a set of skills to solve problems or make decisions, both for academics and for personal interests, through the process of finding, finding and utilizing information from various sources and communicating this new knowledge efficiently, effectively and ethically. The study was conducted with a quantitative approach. The quantitative approach is intended to obtain information about how to literate student information at PTKIN. The study was conducted on users in the library of Sunan Ampel UIN Surabaya. Sample of UIN Sunan Ampel library as many as 167 pemusataka. The sampling method is simple random sampling. The score of users' information literacy ability at UIN Sunan Ampel is 2.864, in the high category. The abilities that need to be improved are (1). The ability to use search / search techniques (Boolean symbols such as AND, OR, NOT) or other symbols when searching for information / references on the Internet (2) the ability to compare information sources originating from print and electronic media (3). The ability to use the style of environment (such as APA, MLA, Chicago, IEEE etc.) correctly when writing bibliography (4) the ability to produce original work (not copy and paste), (5) using bibliographic software (such as Zotero, Mendely) when searching reference and save it (6) The ability to convey ideas or scientific work or information obtained in print or electronic media. The inhibiting factor in the development of information literacy is the ability of information literacy of HR (employees or officers) is still weak. INDONESIA Penelitian ini bertujuan untuk mengkaji bagaimana literasi informasi mahasiswa di UIN Sunan Ampel Surabaya. Literasi informasi merupakan seperangkat keterampilan untuk memecahkan masalah ataupun membuat keputusan, baik untuk kepentingan akademisi ataupun pribadi, melalui proses pencarian, penemuan dan pemanfaatan informasi dari beragam sumber serta mengkomunikasikan pengetahuan baru ini dengan efisien, efektif dan beretika. Penelitian dilakukan dengan pendekatan kuantitatif. Pendekatan kuantitatif dimaksudkan untuk mendapatkan informasi tentang bagaimana literasi informasi mahasiswa di PTKIN. Penelitian dilakukan pada pemustaka di perpustakaan UIN Sunan Ampel Surabaya. Sampel pemustaka UIN Sunan Ampel sebanyak 167 pemusataka. Metode pengambilana sampel adalah simple random sampling. Skor kemampuan literasi informasi pemustaka di UIN Sunan Ampel sebesar 2,864, masuk pada kategori tinggi. Kemampuan yang perlu ditingkatkan adalah adalah (1). Kemampuan menggunakan teknik penelusuran/pencarian (simbol Boolean seperti AND, OR, NOT) atau simbol lain ketika mencari informasi/referensi di Internet (2) kemampuan membandingkan sumber informasi yang berasal dari media cetak dan media elektronik (3). Kemampuan menggunakan gaya selingkung (seperti APA, MLA, Chicago, IEEE dsb) dengan tepat ketika menulis daftar pustaka (4) kemampuan menghasilkan karya yang orisinal (tidak melakukan copy paste), (5) menggunakan software bibliografi (seperti Zotero, Mendely) ketika mencari referensi dan menyimpannya (6) Kemampuan menyampaikan ide atau karya ilmiah atau informasi yang didapat kedalam media cetak atau elektronik.. Faktor penghambat dalam pengembangan literasi informasi adalah kemampuan literasi informasi SDM (pegawai atau petugas) masih lemah.